THE IMPLEMENTATION OF THE SHARED LEADERSHIP MODEL TO DEVELOP EMPLOYEE PERFORMANCE - Cahyaningrum, Desy Dwi; Khusniyah, Nur; Noermijati (Universitas Brawijaya, Indonesia, 2022)
This study aims to uncover and understand the application of the Shared Leadership pattern in managing PIER, to know the Shared Leadership model applied by management in managing PIER, and to reveal and understand the performance of PIER employees by applying the Shared Leadership pattern. This study uses a qualitative research method of a case study approach. The research informant is the department head and PIER staff. The research findings show that the application of Shared Leadership patterns in improving employee performance is derived from the themes contained in the attributes of Shared Leadership, including learning systems, leadership systems, and motivation systems. Shared Purpose, including personality, attitude, and ability. Social Support, including resources, organisational structure, organisational support, and awards. Voice, including expertise, perception, effort, and individual attributes. Shared purpose, social support and voice can create knowledge-sharing and work environments to improve employee performance. Further studies are needed on shared leadership in the same model applied to different objects.